2001
DOI: 10.1112/s1461157000000772
|View full text |Cite
|
Sign up to set email alerts
|

Primes in Elliptic Divisibility Sequences

Abstract: Morgan Ward pursued the study of elliptic divisibility sequences, originally initiated by Lucas, and Chudnovsky and Chudnovsky subsequently suggested looking at elliptic divisibility sequences for prime appearance. The problem of prime appearance in these sequences is examined here, from both a theoretical and a practical viewpoint. We show calculations, together with a heuristic argument, to suggest that these sequences contain only finitely many primes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 16 publications
1
75
0
Order By: Relevance
“…The arithmetical properties of EDS and Somos sequences -in particular the distribution of primes therein -are a subject of current interest [10,11,49]. Some of these properties are discussed in the book [12] (see section 1.1.20, for instance), where it is suggested that such bilinear recurrences should be suitable generalizations of linear ones, with many analogous features.…”
Section: Somos Sequences and The Laurent Propertymentioning
confidence: 99%
“…The arithmetical properties of EDS and Somos sequences -in particular the distribution of primes therein -are a subject of current interest [10,11,49]. Some of these properties are discussed in the book [12] (see section 1.1.20, for instance), where it is suggested that such bilinear recurrences should be suitable generalizations of linear ones, with many analogous features.…”
Section: Somos Sequences and The Laurent Propertymentioning
confidence: 99%
“…Ward, who made an extensive study of these sequences [24,25], shows that a proper elliptic divisibility sequence W is associated to a (possibly singular) elliptic curve E W and point P W ∈ E W (Q) and that the values of W n are closely related to the values of the division polynomials F n (P W ). More recently, elliptic divisibility sequences have been studied by Shipsey [19], who gives an application to the elliptic curve discrete logarithm problem, and by several other authors [3,4,5,8,9,10,23,22]. (See also [11,13,14] for work on the related Somos sequences.)…”
Section: Theorem 3 With Notation and Assumptions As Inmentioning
confidence: 99%
“…It is easy to check that it suffices that (W n ) satisfy the two relations [24].) Additional material on elliptic divisibility sequences may be found in [4,5,8,9,10,19,23,22,24,25].…”
Section: Elliptic Divisibility Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…See for instance [EEW01] or [Rey12] and the references therein. In this paper we derive strong conditions on the denominators d P from the uniform abc-conjecture over number fields (see Conjecture 2.2 or [GS00]).…”
Section: Introductionmentioning
confidence: 99%